When Nations Can't Default: A History of War Reparations and Sovereign Debt - Chatterjee, Satyajit (Journal of Economic Literature, 2024)
Satyajit Chatterjee of Federal Reserve Bank of Philadelphia reviews “When Nations Can't Default: A History of War Reparations and Sovereign Debt” by Simon Hinrichson. The Econlit abstract of this book begins: “Promotes the argument that war reparations are unlike other sovereign debt because the repayment is enforced by military and political force, exploring how debtor countries end up in suboptimal economic situations that do not occur during normal sovereign debt management.”